Synthesis, Microstructure and Magnetic Properties of Soft Magnetic CoP Films - S. A. Podorozhnyak; A. V. Ryzhenkov; T. N. Patrusheva; M. N. Volochaev; A. V. Chzhan (Известия высших учебных заведений России: Радиоэлектроника)
Soft magnetic thin CoP films were obtained by means of chemical metallization from aqueous cobalt salt solution in the presence of sodium hydroxide, citric acid and sodium hypophosphite as the reducing agent. The optimal values of the magnetic film parameters (saturation magnetization and width of ferromagnetic resonance line) were obtained by variation of composition of work solutions. It allows to reduce losses in their application in microwave devices. Microphotographs of magnetic film indicate a grain structure with a grain size of about 50 nm and presence of inclusions with the size of 3-5 nm. To determine the magnetic parameters of the investigated films the method of ferromagnetic resonance (FMR) absorption curves processing is used. The values of FMR line width and an effective magnetization of film material saturation were obtained.